Primer Design and in Silico PCR for Detection Shigella Sp. on Refilled Water Samples - Deratih Bunga Purwakasih (Serambi Biologi, 2021)
Refillable drinking water is an effort to meet the needs of drinking water for consumption by modern society. One of the quality parameters of drinking water suitable for consumption is not contaminated with Escherichia coli, Salmonella sp. and Shigella sp. Conventional microbiological tests were often conducted for the detection of water pathogenic bacteria, including culturing the bacteria in medium culture and biochemical assay, but this method requires a long working time and expensive costs. Currently, Polymerase Chain Reactions (PCR) can be an alternative method because it has high accuracy. Primers are one of the important components of PCR so they must be specifically designed to ensure the success of DNA amplification. This study aimed to obtain the specific sequence of PCR primer for detection Shigella-contaminated refillable drinking water sample and conducted the in silico PCR. Primers were designed in silico using Primer BLAST in NCBI (National Center for Biotechnology Information) and Geneious Prime for in silico PCR. To get a Shigella-specific primer, pairwise alignment of Shigella sp. (NC_004337.2) and E.coli (NC_000913.3) was performed and specific sequence of Shigella was used as primer candidates. The result of this study were the Shigella-specific sequence PCR primer forward 5'-GCTAATGAAAATGGCGCTGT-3' and reverse 5'-AGCCGACGGTTTGAAGTTAC-3' with PCR product length of 815 bp.